Solid tire production process and industrial forklift solid tire
Through specific rubber composite formulas and wear-resistant and anti-slip fillers, the mechanical properties and wear resistance of solid tires are improved, and the problems of insufficient mechanical properties, wear resistance and slip resistance of existing tires are solved. They are suitable for industrial forklifts and extended Service life.
Patent Information
- Application Number
- CN202411039998.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing solid tires have shortcomings in mechanical properties, wear resistance and slip resistance, which are difficult to meet the high requirements of industrial forklifts, and their durability and safety need to be further improved.
Use specific rubber composite formulas and wear-resistant and anti-slip fillers, including natural rubber, styrene butadiene rubber, nitrile rubber, ethylene propylene rubber, modified carbon black and carbon fiber. Through the combination of vulcanizing agent and accelerator, the mechanics of the tread rubber are improved. Performance and slippery resistance, and enhance the wear resistance of the tires by the use of modified carbon black and boron nitride.
It significantly improves the mechanical properties, wear resistance and slip resistance of solid tires, extends the service life, making it more suitable for industrial forklifts, and has good application prospects.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid tires, and in particular relates to a solid tire production process and an industrial forklift solid tire. Background Art
[0002] As a major component of a forklift, tires have a significant impact on the forklift's traction performance, operating stability and safety, braking performance, and operating efficiency. Their performance should meet the requirements of high strength, large load-bearing capacity, good wear resistance, and good ground adhesion. Their functions are: (1) to bear the weight of the forklift body, as well as the weight of the operator and cargo; (2) to use the friction between the tire and the ground to achieve vehicle operation and steering; (3) to absorb vibration and impact during operation to maintain operational stability.
[0003] With the vigorous development of forklifts and their wide application in various industries, their safety and durability have also become important indicators for measuring forklift performance. For example, there are out-of-control accidents caused by slipping due to severe wear of the driving tire surface during forklift driving, rollover accidents caused by tire rupture during forklift operation, and tire burst injuries. Therefore, the reasonable selection of forklift tires and appropriate tire inspection methods play a vital role in ensuring the safe operation of forklifts.
[0004] Chinese patent CN114163703A discloses a durable solid tire and its preparation method. The durable solid tire includes a tire liner and a tread rubber. The tire liner includes the following components: chloroprene rubber, reclaimed rubber, natural rubber, antioxidant, sulfur, and accelerator; the tread rubber includes the following raw materials: butadiene rubber, chloroprene rubber, reclaimed rubber, carbon black, amide-grafted modified polyethylene terephthalate, zinc oxide, sulfur, and stearic acid; and its preparation method is as follows: S1. Preparation of tire liner; S2. Preparation of tread rubber; S3. Preparation of solid tire. The invention adopts amide-grafted modified polyethylene terephthalate to improve the thermal conductivity of the tread rubber, and forms hydrogen bonds between the ester group and the amide group in its structure to hinder the movement of the chain segments, thereby improving the wear resistance of the tread rubber and extending the service life of the tire. Adding reclaimed rubber to the tire liner and tread rubber can reduce the use of natural rubber and has certain energy-saving and environmental protection effects. However, this invention mainly improves the wear resistance and thermal conductivity of solid tires, and the mechanical properties and anti-skid properties of tires need to be further improved. Moreover, since forklifts need to move forward and backward continuously during operation, they have higher requirements for the wear resistance and anti-skid properties of tires. Whether the solid tires of this invention are suitable for forklifts remains to be discussed.
[0005] Chinese patent CN102504379A discloses a solid tire composition prepared by using tire scraps, which is composed of the following substances in weight percentage: unvulcanized tire scraps: 60-80%, vulcanized reclaimed rubber: 15-40%, accelerator: 1-2%, antioxidant: 1-2%, adhesive: 1-2%, zinc oxide: 0-2%, carbon black: 0-2%, stearic acid: 0-2%, softener: 0-2%, resin: 0-2%, and has the advantages that the solid tire produced by the formula of the invention has low cost and good product quality, and is suitable for making solid tires of various specifications. The solid tire has low cost and good quality, but the mechanical properties and wear resistance of the solid tire cannot be known from the patent text, so it is impossible to determine whether it is suitable for forklift tires.
[0006] Based on this, developing a solid tire with good mechanical properties, good wear resistance and excellent anti-skid performance is of great significance to the field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a solid tire production process and an industrial forklift solid tire. The solid tire has good mechanical properties and wear resistance, as well as good anti-skid and aging resistance, which extends the service life of the solid tire. The solid tire is very suitable for industrial forklift solid tires and has good application prospects.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A solid tire, comprising a tire liner and a tread rubber;
[0010] The tire liner comprises the following raw materials in parts by weight: 80-100 parts of natural rubber, 40-50 parts of butadiene rubber, 15-25 parts of carbon black, 2-4 parts of vulcanizing agent, 3-6 parts of zinc oxide, 2-5 parts of stearic acid, 1-2 parts of silane coupling agent, 0.5-1.5 parts of accelerator, and 0.5-0.8 parts of antioxidant;
[0011] The tread rubber comprises the following raw materials in parts by weight: 60-80 parts of natural rubber, 40-50 parts of styrene-butadiene rubber, 20-30 parts of nitrile rubber, 5-10 parts of ethylene-propylene rubber, 1-3 parts of vulcanizer, 0.5-2 parts of accelerator, 25-35 parts of modified carbon black, 15-30 parts of anti-skid and wear-resistant agent, 2-5 parts of zinc oxide, 3-6 parts of stearic acid, 3-5 parts of filler oil and 0.4-0.7 parts of antioxidant.
[0012] In the present invention, the tread rubber is compounded with four kinds of rubber in a specific ratio, which not only improves the mechanical properties of the rubber surface rubber, but also improves its anti-skid property, so that the solid tire has good comprehensive performance. Natural rubber has excellent mechanical properties, flex fatigue resistance, wet skid resistance, low temperature resistance, wear resistance, good processing performance, small hysteresis loss, low heat generation under multiple deformations, good compatibility with other rubbers, and excellent comprehensive performance; styrene-butadiene rubber has good processing performance, excellent wear resistance, wet skid resistance, heat resistance and aging resistance; nitrile rubber is a copolymer formed by the polymerization of acrylonitrile and butadiene monomers, mainly produced by low-temperature emulsion polymerization, with excellent oil resistance, high wear resistance, good heat resistance, strong adhesion, and excellent wet skid resistance; EPDM rubber has excellent aging resistance such as ozone resistance, heat resistance, weather resistance, etc., and has good chemical resistance, electrical insulation performance, impact elasticity, low temperature performance, low density and high filling capacity, as well as hot water resistance and water vapor resistance, etc., which can improve the weather resistance, heat resistance and cold resistance of tires, extend service life, and improve the overall performance of tread rubber.
[0013] Preferably, the vulcanizing agent is sulfur; the silane coupling agent is one or more of KH550, KH560, and KH570; the accelerator is one or more of accelerator D, accelerator CZ, accelerator TMTM, and accelerator TMTD; the filler oil is cyclohexane oil or white oil; and the antioxidant is one or more of antioxidant 4020, antioxidant RD, and antioxidant NA.
[0014] Preferably, the method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0015] S1, adding carbon fiber to deionized water, then adding melamine, boric acid, ammonium molybdate, and sodium dodecyl sulfate, stirring to react, filtering, washing, drying, and calcining under a nitrogen atmosphere to obtain composite carbon fiber;
[0016] S2, adding the composite carbon fiber in step S1 to an ethanol aqueous solution, then adding γ-glycidyloxypropyltrimethoxysilane, heating to react, filtering, washing, and drying after the reaction is completed to obtain a modified carbon fiber;
[0017] S3, adding toluene to the modified carbon fiber in step S2, and then adding phenolic resin and triethylamine, and reacting at a constant temperature under a nitrogen atmosphere. After the reaction is completed, filtering, washing, and drying are performed to obtain the wear-resistant and anti-skid filler.
[0018] Preferably, in step S1, the mass ratio of carbon fiber, melamine, boric acid, ammonium molybdate and sodium dodecyl sulfate is 50-60:30-40:15-20:20-30:10-20, the stirring reaction temperature is 90-100°C, and the time is 4-6h; the calcination temperature is 800-900°C, and the time is 3-5h.
[0019] In the present invention, the added wear-resistant and anti-skid filler is based on carbon fiber. The structure of the carbon fiber is a low-graphitization chaotic graphite structure, which belongs to a heterogeneous structure. The basic hexagonal mesh plane structural unit makes it have the characteristics of high specific strength, large specific modulus, good thermal conductivity, etc. By in-situ generating boron nitride and molybdenum oxide on its surface, the wear resistance of the composite carbon fiber is significantly improved. At the same time, boron nitride and molybdenum oxide can also improve the surface roughness of the carbon fiber, improve the bonding strength between the carbon fiber and the rubber substrate, and increase the mechanical properties and wear resistance of the tread rubber.
[0020] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution in step S2 is 7-8:2-3, the mass ratio of the composite carbon fiber and γ-glycidyloxypropyltrimethoxysilane is 50-60:4-8, the temperature of the heating reaction is 50-60°C, and the time is 2-3h.
[0021] In the present invention, the composite carbon fiber is modified by using γ-glycidyloxypropyltrimethoxysilane, thereby improving the dispersibility of the carbon fiber and introducing active groups on the surface of the carbon fiber, which is beneficial to the subsequent reaction.
[0022] Preferably, in step S3, the mass ratio of the modified carbon fiber, phenolic resin and triethylamine is 50-60:20-30:30-40, the temperature of the isothermal reaction is 70-80° C., and the time is 1-3 h.
[0023] In the present invention, the modified carbon fiber is reacted with the phenolic resin, and the epoxy group on the modified carbon fiber and the hydroxyl group on the phenolic resin are combined with each other through covalent bonds under the action of triethylamine, so that the phenolic resin is introduced into the carbon fiber, thereby improving the compatibility of the carbon fiber and the rubber matrix, and improving the interface strength between the two, thereby increasing the mechanical properties and wear resistance of the rubber surface, and at the same time, the introduced phenolic resin can also synergistically act with the nitrile rubber, significantly improving the anti-slip performance of the rubber surface.
[0024] Preferably, the preparation method of the modified carbon black is as follows:
[0025] 20-30g of zirconium oxychloride is added to 200-300g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black is added. After stirring evenly, ammonia water with a mass concentration of 10% is added to adjust the pH to 9-10, and the mixture is stirred at 30-40°C for 2-3h. After stirring, the mixture is filtered, dried, and calcined under a nitrogen atmosphere to obtain composite carbon black; 50-60g of composite carbon black is added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 5-10g of γ-aminopropyltriethoxysilane is added. The mixture is stirred at 60-70°C for 2-3h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain amino carbon black; 50-60g of amino carbon black is added to DMF, and then 5-10g of 2-(trifluoromethyl)cinnamic acid and 1-3g of p-toluenesulfonic acid are added. The mixture is reacted at 90-100°C for 3-4h. After the reaction is completed, the modified carbon black is obtained.
[0026] In the present invention, the rubber has poor comprehensive properties such as strength, hardness and wear resistance due to its large free volume, small intermolecular force and lack of crystallization ability. By adding carbon black as a reinforcing agent, the comprehensive properties of the tread rubber can be effectively improved. Zirconium oxide is generated in situ on the surface of carbon black by a sol method, which further improves the wear resistance of carbon black. The composite carbon black is then amino-modified to improve its dispersibility. Then the amino carbon black is reacted with 2-(trifluoromethyl)cinnamic acid to introduce 2-(trifluoromethyl)cinnamic acid on the surface of carbon black. The fluoromethyl group in 2-(trifluoromethyl)cinnamic acid has high chemical stability and can improve the anti-oxidation and anti-corrosion ability of the tread rubber. At the same time, the fluoromethyl group can improve the compatibility of carbon black and rubber matrix, and enhance the interfacial adhesion between carbon black and rubber, thereby improving the overall mechanical properties and wear resistance of the tread rubber. In addition, the double bonds contained in 2-(trifluoromethyl)cinnamic acid can form covalent bonds with the rubber substrate during the tire vulcanization process, further improving the mechanical properties of the tire.
[0027] The present invention also protects a method for preparing the solid tire as described above, comprising the following steps:
[0028] (1) Preparation of tire liner: weigh raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once, then add carbon black, zinc oxide, stearic acid, silane coupling agent, and antioxidant, mix them twice, then add vulcanizing agent and accelerator, mix them three times, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0029] (2) Preparation of tread rubber: weighing raw materials according to the formula, adding natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mixing once, then adding antioxidant, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and filler oil, mixing twice, then adding vulcanizing agent and accelerator, mixing three times, after mixing, adding the tread rubber material into a mold to obtain a tread rubber layer;
[0030] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 50-60°C for 2-4 hours, and then placed in a mold and vulcanized to obtain the solid tire.
[0031] Preferably, in step (1), the temperature of the first mixing is 60-70°C, the time is 5-8 min, the temperature of the second mixing is 60-70°C, the time is 6-10 min, and the temperature of the third mixing is 140-160°C, the time is 10-15 min; in step (2), the temperature of the first mixing is 60-70°C, the time is 5-8 min, the temperature of the second mixing is 70-80°C, the time is 4-6 min, and the temperature of the third mixing is 120-140°C, the time is 10-15 min; in step (3), the vulcanization temperature is 140-150°C, the time is 3-5 h.
[0032] The present invention also protects an industrial forklift solid tire, which is prepared by using the solid tire as described above.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The solid tire provided by the present invention has a tread rubber that not only improves the mechanical properties of the rubber surface rubber, but also improves its anti-skid property by compounding four types of rubber in a specific proportion, so that the solid tire has good comprehensive performance. The wear-resistant and anti-skid filler and modified carbon black added to the tread rubber can well combine the rigidity of carbon fiber with the flexibility of rubber, so that the tread rubber has excellent properties such as high modulus, high tear strength, low heat generation, and creep resistance. It not only improves the mechanical properties and wear resistance of the solid tire, but also improves the anti-skid and aging resistance of the solid tire, and extends the service life of the solid tire. The solid tire is very suitable for industrial forklift solid tires and has good application prospects.
[0035] (2) The wear-resistant and anti-skid filler prepared by the solid tire provided by the present invention takes carbon fiber as the substrate, and generates boron nitride and molybdenum oxide in situ on the surface of the carbon fiber, thereby significantly improving the wear resistance of the composite carbon fiber. At the same time, boron nitride and molybdenum oxide can also increase the surface roughness of the carbon fiber, thereby improving the bonding strength between the carbon fiber and the rubber substrate, and increasing the mechanical properties and wear resistance of the tread rubber. Subsequently, a phenolic resin is introduced into the surface of the modified carbon fiber by a chemical grafting method, thereby improving the compatibility of the carbon fiber and the rubber matrix, thereby improving the interface strength between the two, thereby increasing the mechanical properties and wear resistance of the rubber surface. At the same time, the introduced phenolic resin can also synergistically act with nitrile rubber, thereby significantly improving the anti-slip performance of the rubber surface.
[0036] (3) In the solid tire provided by the present invention, the modified carbon black is added, and zirconium oxide is generated in situ on the surface of the carbon black by a sol method, thereby further improving the wear resistance of the carbon black. Subsequently, the composite carbon black is subjected to amino modification to improve its dispersibility. Then, the amino carbon black is reacted with 2-(trifluoromethyl)cinnamic acid to introduce 2-(trifluoromethyl)cinnamic acid on the surface of the carbon black. The fluoromethyl group in the 2-(trifluoromethyl)cinnamic acid has a high chemical stability and can improve the oxidation resistance and corrosion resistance of the tread rubber. At the same time, the fluoromethyl group can improve the compatibility of the carbon black and the rubber matrix and enhance the interfacial adhesion between the carbon black and the rubber, thereby improving the overall mechanical properties and wear resistance of the tread rubber. In addition, the double bonds contained in the 2-(trifluoromethyl)cinnamic acid can form covalent bonds with the rubber substrate during the tire vulcanization process, thereby further improving the mechanical properties of the tire. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the present invention, the natural rubber is purchased from Hainan Natural Rubber Co., Ltd. and is 5# standard rubber; the cis-1,4-butadiene rubber is purchased from Shandong Ousheng Chemical Co., Ltd. and is brand BR9000; the styrene-butadiene rubber is purchased from Sinopec Qilu Co., Ltd. and is brand 1502; the nitrile rubber is purchased from Guangzhou Tianbenfeng Rubber Co., Ltd. and is brand Lanhua nitrile rubber NBR N41E; the ethylene-propylene rubber is ethylene-propylene-diene rubber, purchased from Dongguan Chengjin Plastics Co., Ltd. and is brand SKS5890F of South Korea, with an ethylene content of 68wt% and a Mooney viscosity of 64MU; the carbon fiber is purchased from Shanghai Lishuo Composite Materials Technology Co., Ltd. and has a diameter of 6-7μm and a length of 6-10mm; the carbon black is purchased from Shandong Wanhua Tianhe New Materials Co., Ltd. and is model N330 with a mesh size of 1250 meshes; the phenolic resin is purchased from Jinan Dahui Chemical Technology Co., Ltd. and is model 2402 phenolic resin with a hydroxymethyl content of 9%-15%.
[0039] Example 1
[0040] A solid tire, comprising a tire liner and a tread rubber;
[0041] The tire liner comprises the following raw materials in parts by weight: 90 parts of natural rubber, 45 parts of butadiene rubber, 20 parts of carbon black, 3 parts of sulfur, 5 parts of zinc oxide, 4 parts of stearic acid, 1.5 parts of KH550, 1 part of accelerator D, and 0.7 parts of antioxidant 4020;
[0042] The tread rubber comprises the following raw materials in parts by weight: 70 parts of natural rubber, 45 parts of styrene-butadiene rubber, 25 parts of nitrile rubber, 8 parts of ethylene-propylene rubber, 2 parts of sulfur, 1 part of accelerator CZ, 30 parts of modified carbon black, 25 parts of anti-skid and wear-resistant agent, 4 parts of zinc oxide, 5 parts of stearic acid, 3-5 parts of cyclohexane oil, and 0.6 parts of antioxidant 4020.
[0043] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0044] S1. Add 55g of carbon fiber to 1L of deionized water, then add 35g of melamine, 18g of boric acid, 25g of ammonium molybdate, and 15g of sodium dodecyl sulfate, and stir at 95°C for 5h. After the reaction is completed, filter, wash, and dry, and calcine under a nitrogen atmosphere at a temperature of 850°C for 4h to obtain a composite carbon fiber;
[0045] S2, adding 55g of the composite carbon fiber in step S1 to 800mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7:3), then adding 6g of γ-glycidyloxypropyltrimethoxysilane, reacting at 55°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain modified carbon fiber;
[0046] S3. Add 55 g of modified carbon fiber in step S2 into 900 mL of toluene, and then add 25 g of phenolic resin and 35 g of triethylamine. Under a nitrogen atmosphere, react at 75° C. for 2 h. After the reaction is completed, filter, wash, and dry to obtain the wear-resistant and anti-skid filler.
[0047] The preparation method of the modified carbon black is as follows:
[0048] 25g of zirconium oxychloride was added to 250g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black was added. After stirring, 10% ammonia water was added to adjust the pH to 10, and the mixture was stirred at 35°C for 2.5h. After stirring, the mixture was filtered and dried, and calcined under a nitrogen atmosphere at 550°C for 3h to obtain composite carbon black. 55g of composite carbon black was added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 8g of γ-aminopropyltriethoxysilane was added. The mixture was stirred at 65°C for 2.5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain amino carbon black. 55g of amino carbon black was added to DMF, and then 8g of 2-(trifluoromethyl)cinnamic acid and 2g of p-toluenesulfonic acid were added. The mixture was reacted at 95°C for 3.5h. After the reaction was completed, the modified carbon black was obtained.
[0049] A production process for a solid tire comprises the following steps:
[0050] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once at 65° C. for 7 min, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH550, and antioxidant 4020, mix them twice at 65° C. for 8 min, then add sulfur and accelerator D, mix them three times at 150° C. for 13 min, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0051] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 65° C. for 6 min, then add antioxidant 4020, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and cyclohexane oil, mix them twice at 75° C. for 5 min, then add sulfur and accelerator CZ, mix them three times at 130° C. for 13 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0052] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 55°C for 3 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0053] Example 2
[0054] A solid tire, comprising a tire liner and a tread rubber;
[0055] The tire liner comprises the following raw materials in parts by weight: 80 parts of natural rubber, 40 parts of butadiene rubber, 15 parts of carbon black, 2 parts of sulfur, 3 parts of zinc oxide, 2 parts of stearic acid, 1 part of KH560, 0.5 parts of accelerator CZ, and 0.5 parts of antioxidant RD;
[0056] The tread rubber comprises the following raw materials in parts by weight: 60 parts of natural rubber, 40 parts of styrene-butadiene rubber, 20 parts of nitrile rubber, 5 parts of ethylene-propylene rubber, 1 part of sulfur, 0.5 parts of accelerator TMTM, 25 parts of modified carbon black, 15 parts of anti-skid and wear-resistant agent, 2 parts of zinc oxide, 3 parts of stearic acid, 3 parts of white oil, and 0.4 parts of antioxidant RD.
[0057] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0058] S1. Add 50g of carbon fiber to 1L of deionized water, then add 30g of melamine, 15g of boric acid, 20g of ammonium molybdate, and 10g of sodium dodecyl sulfate, and stir at 90°C for 6h. After the reaction is completed, filter, wash, and dry, and calcine under a nitrogen atmosphere at a temperature of 800°C for 5h to obtain a composite carbon fiber;
[0059] S2, adding 50g of the composite carbon fiber in step S1 to 800mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7:3), then adding 4g of γ-glycidyloxypropyltrimethoxysilane, reacting at 50°C for 3h, filtering, washing and drying after the reaction is completed to obtain modified carbon fiber;
[0060] S3. Add 50 g of modified carbon fiber in step S2 into 900 mL of toluene, and then add 20 g of phenolic resin and 30 g of triethylamine. Under a nitrogen atmosphere, react at 70° C. for 3 h. After the reaction is completed, filter, wash, and dry to obtain the wear-resistant and anti-skid filler.
[0061] The preparation method of the modified carbon black is as follows:
[0062] 20g of zirconium oxychloride is added to 200g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black is added. After stirring evenly, ammonia water with a mass concentration of 10% is added to adjust the pH to 9, and the mixture is stirred at 30°C for 3h. After stirring, the mixture is filtered and dried, and calcined under a nitrogen atmosphere at 500°C for 4h to obtain composite carbon black; 50g of composite carbon black is added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 5g of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at 60°C for 3h. After the reaction is completed, the mixture is filtered, washed and dried to obtain amino carbon black; 50g of amino carbon black is added to DMF, and then 5g of 2-(trifluoromethyl)cinnamic acid and 1g of p-toluenesulfonic acid are added, and the mixture is reacted at 90°C for 4h. After the reaction is completed, the modified carbon black is obtained.
[0063] A production process for a solid tire comprises the following steps:
[0064] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them for 8 min at 60°C, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH560, and antioxidant RD, mix them for a second time at 60°C for 10 min, then add sulfur and accelerator CZ, mix them for a third time at 140-160°C for 15 min, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0065] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 60° C. for 5 min, then add antioxidant RD, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and white oil, mix them twice at 70° C. for 6 min, then add sulfur and accelerator TMTM, mix them three times at 120° C. for 10 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0066] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 50°C for 4 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0067] Example 3
[0068] A solid tire, comprising a tire liner and a tread rubber;
[0069] The tire liner includes the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of butadiene rubber, 25 parts of carbon black, 4 parts of sulfur, 6 parts of zinc oxide, 5 parts of stearic acid, 2 parts of KH570, 1.5 parts of accelerator TMTM, and 0.8 parts of antioxidant NA;
[0070] The tread rubber includes the following raw materials in parts by weight: 80 parts of natural rubber, 50 parts of styrene-butadiene rubber, 30 parts of nitrile rubber, 10 parts of ethylene-propylene rubber, 3 parts of sulfur, 2 parts of accelerator TMTD, 35 parts of modified carbon black, 30 parts of anti-skid and wear-resistant agent, 5 parts of zinc oxide, 6 parts of stearic acid, 5 parts of cyclohexane oil, and 0.7 parts of antioxidant NA.
[0071] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0072] S1. Add 60g of carbon fiber to 1L of deionized water, then add 40g of melamine, 20g of boric acid, 30g of ammonium molybdate, and 20g of sodium dodecyl sulfate, and stir at 100°C for 4h. After the reaction is completed, filter, wash, and dry, and calcine under a nitrogen atmosphere at a temperature of 900°C for 3h to obtain a composite carbon fiber;
[0073] S2, adding 60g of the composite carbon fiber in step S1 to 800mL of ethanol aqueous solution (the volume ratio of ethanol to water is 8:2), then adding 8g of γ-glycidyloxypropyltrimethoxysilane, reacting at 60°C for 2h, filtering, washing and drying after the reaction is completed to obtain modified carbon fiber;
[0074] S3. Add 60 g of modified carbon fiber in step S2 into 900 mL of toluene, and then add 30 g of phenolic resin and 40 g of triethylamine. Under a nitrogen atmosphere, react at 80° C. for 1 h. After the reaction is completed, filter, wash, and dry to obtain the wear-resistant and anti-skid filler.
[0075] The preparation method of the modified carbon black is as follows:
[0076] 30g of zirconium oxychloride is added to 300g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black is added. After stirring evenly, ammonia water with a mass concentration of 10% is added to adjust the pH to 10, and the mixture is stirred at 40°C for 2h. After stirring, the mixture is filtered and dried, and calcined under a nitrogen atmosphere at 600°C for 2h to obtain composite carbon black; 60g of composite carbon black is added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 10g of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at 70°C for 2h. After the reaction is completed, the mixture is filtered, washed and dried to obtain amino carbon black; 60g of amino carbon black is added to DMF, and then 10g of 2-(trifluoromethyl)cinnamic acid and 3g of p-toluenesulfonic acid are added, and the mixture is reacted at 100°C for 3h. After the reaction is completed, the modified carbon black is obtained.
[0077] A production process for a solid tire comprises the following steps:
[0078] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them at 70°C for 5 minutes, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH570, antioxidant NA, mix them at 70°C for 6 minutes, then add sulfur and accelerator TMTM, mix them at 160°C for 10 minutes, after mixing, add the tire rubber into a mold to obtain a tire liner;
[0079] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 70° C. for 5 min, then add antioxidant NA, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and cyclohexane oil, mix them twice at 80° C. for 4 min, then add sulfur and accelerator TMTD, mix them three times at 140° C. for 15 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0080] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 60°C for 2 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0081] Comparative Example 1
[0082] A solid tire, comprising a tire liner and a tread rubber;
[0083] The tire liner comprises the following raw materials in parts by weight: 90 parts of natural rubber, 45 parts of butadiene rubber, 20 parts of carbon black, 3 parts of sulfur, 5 parts of zinc oxide, 4 parts of stearic acid, 1.5 parts of KH550, 1 part of accelerator D, and 0.7 parts of antioxidant 4020;
[0084] The tread rubber comprises the following raw materials in parts by weight: 70 parts of natural rubber, 45 parts of styrene-butadiene rubber, 25 parts of nitrile rubber, 8 parts of ethylene-propylene rubber, 2 parts of sulfur, 1 part of accelerator CZ, 30 parts of composite carbon black, 25 parts of anti-skid and wear-resistant agent, 4 parts of zinc oxide, 5 parts of stearic acid, 3-5 parts of cyclohexane oil, and 0.6 parts of antioxidant 4020.
[0085] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0086] S1. Add 55g of carbon fiber to 1L of deionized water, then add 35g of melamine, 18g of boric acid, 25g of ammonium molybdate, and 15g of sodium dodecyl sulfate, and stir at 95°C for 5h. After the reaction is completed, filter, wash, and dry, and calcine under a nitrogen atmosphere at a temperature of 850°C for 4h to obtain a composite carbon fiber;
[0087] S2, adding 55g of the composite carbon fiber in step S1 to 800mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7:3), then adding 6g of γ-glycidyloxypropyltrimethoxysilane, reacting at 55°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain modified carbon fiber;
[0088] S3. Add 55 g of modified carbon fiber in step S2 into 900 mL of toluene, and then add 25 g of phenolic resin and 35 g of triethylamine. Under a nitrogen atmosphere, react at 75° C. for 2 h. After the reaction is completed, filter, wash, and dry to obtain the wear-resistant and anti-skid filler.
[0089] The preparation method of the composite carbon black is as follows:
[0090] Add 25g of zirconium oxychloride to 250g of 5% hydrochloric acid solution, then add 50g of carbon black, stir evenly, add 10% ammonia water to adjust the pH to 10, stir at 35°C for 2.5h, filter and dry after stirring, calcine in a nitrogen atmosphere at 550°C for 3h to obtain composite carbon black.
[0091] A production process for a solid tire comprises the following steps:
[0092] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once at 65° C. for 7 min, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH550, and antioxidant 4020, mix them twice at 65° C. for 8 min, then add sulfur and accelerator D, mix them three times at 150° C. for 13 min, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0093] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 65° C. for 6 min, then add antioxidant 4020, composite carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and cyclohexane oil, mix them twice at 75° C. for 5 min, then add sulfur and accelerator CZ, mix them three times at 130° C. for 13 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0094] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 55°C for 3 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0095] Comparative Example 2
[0096] A solid tire, comprising a tire liner and a tread rubber;
[0097] The tire liner comprises the following raw materials in parts by weight: 90 parts of natural rubber, 45 parts of butadiene rubber, 20 parts of carbon black, 3 parts of sulfur, 5 parts of zinc oxide, 4 parts of stearic acid, 1.5 parts of KH550, 1 part of accelerator D, and 0.7 parts of antioxidant 4020;
[0098] The tread rubber comprises the following raw materials in parts by weight: 70 parts of natural rubber, 45 parts of styrene-butadiene rubber, 25 parts of nitrile rubber, 8 parts of ethylene-propylene rubber, 2 parts of sulfur, 1 part of accelerator CZ, 30 parts of modified carbon black, 25 parts of anti-skid and wear-resistant agent, 4 parts of zinc oxide, 5 parts of stearic acid, 3-5 parts of cyclohexane oil, and 0.6 parts of antioxidant 4020.
[0099] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0100] 55 g of carbon fiber was added into 800 mL of ethanol-water solution (the volume ratio of ethanol to water was 7:3), and then 6 g of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was reacted at 55° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the wear-resistant and anti-skid filler.
[0101] The preparation method of the modified carbon black is as follows:
[0102] 25g of zirconium oxychloride was added to 250g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black was added. After stirring, 10% ammonia water was added to adjust the pH to 10, and the mixture was stirred at 35°C for 2.5h. After stirring, the mixture was filtered and dried, and calcined under a nitrogen atmosphere at 550°C for 3h to obtain composite carbon black. 55g of composite carbon black was added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 8g of γ-aminopropyltriethoxysilane was added. The mixture was stirred at 65°C for 2.5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain amino carbon black. 55g of amino carbon black was added to DMF, and then 8g of 2-(trifluoromethyl)cinnamic acid and 2g of p-toluenesulfonic acid were added. The mixture was reacted at 95°C for 3.5h. After the reaction was completed, the modified carbon black was obtained.
[0103] A production process for a solid tire comprises the following steps:
[0104] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once at 65° C. for 7 min, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH550, and antioxidant 4020, mix them twice at 65° C. for 8 min, then add sulfur and accelerator D, mix them three times at 150° C. for 13 min, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0105] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 65° C. for 6 min, then add antioxidant 4020, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and cyclohexane oil, mix them twice at 75° C. for 5 min, then add sulfur and accelerator CZ, mix them three times at 130° C. for 13 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0106] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 55°C for 3 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0107] Comparative Example 3
[0108] A solid tire, comprising a tire liner and a tread rubber;
[0109] The tire liner comprises the following raw materials in parts by weight: 90 parts of natural rubber, 45 parts of butadiene rubber, 20 parts of carbon black, 3 parts of sulfur, 5 parts of zinc oxide, 4 parts of stearic acid, 1.5 parts of KH550, 1 part of accelerator D, and 0.7 parts of antioxidant 4020;
[0110] The tread rubber comprises the following raw materials in parts by weight: 70 parts of natural rubber, 45 parts of styrene-butadiene rubber, 25 parts of nitrile rubber, 8 parts of ethylene-propylene rubber, 2 parts of sulfur, 1 part of accelerator CZ, 30 parts of composite carbon black, 25 parts of anti-skid and wear-resistant agent, 4 parts of zinc oxide, 5 parts of stearic acid, 3-5 parts of cyclohexane oil, and 0.6 parts of antioxidant 4020.
[0111] The method for preparing the anti-skid and wear-resistant filler comprises the following steps:
[0112] 55 g of carbon fiber was added into 800 mL of ethanol-water solution (the volume ratio of ethanol to water was 7:3), and then 6 g of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was reacted at 55° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the wear-resistant and anti-skid filler.
[0113] The preparation method of the composite carbon black is as follows:
[0114] Add 25g of zirconium oxychloride to 250g of 5% hydrochloric acid solution, then add 50g of carbon black, stir evenly, add 10% ammonia water to adjust the pH to 10, stir at 35°C for 2.5h, filter and dry after stirring, calcine in a nitrogen atmosphere at 550°C for 3h to obtain composite carbon black.
[0115] A production process for a solid tire comprises the following steps:
[0116] (1) Preparation of tire liner: weigh the raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once at 65° C. for 7 min, then add carbon black, zinc oxide, stearic acid, silane coupling agent KH550, and antioxidant 4020, mix them twice at 65° C. for 8 min, then add sulfur and accelerator D, mix them three times at 150° C. for 13 min, and after mixing, add the tire rubber into a mold to obtain a tire liner;
[0117] (2) Preparation of tread rubber: weigh the raw materials according to the formula, add natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mix them once at 65° C. for 6 min, then add antioxidant 4020, composite carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and cyclohexane oil, mix them twice at 75° C. for 5 min, then add sulfur and accelerator CZ, mix them three times at 130° C. for 13 min, and after mixing, add the tread rubber material into a mold to obtain a tread rubber layer;
[0118] (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 55°C for 3 hours, and then placed in a mold and vulcanized at 150°C for 4 hours to obtain the solid tire.
[0119] The solid tires prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, wherein the tensile strength and elongation at break were tested according to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", with a tensile speed of 500 mm / min and a test temperature of room temperature; tear performance: the tread rubber was tested according to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)", with a tensile speed of 500 mm / min and a test temperature of room temperature; the wear resistance index was tested according to GB / T 22391-2017 "Drum method for durability test of solid tires"; the test results are shown in Table 1 below:
[0120] Table 1
[0121] Tensile strength / MPa Elongation at break / % Trouser tear kN / m Wear resistance index Example 1 26.9 592 18.6 497 Example 2 25.3 547 17.2 485 Example 3 26.2 576 18.1 493 Comparative Example 1 22.1 472 17.4 458 Comparative Example 2 23.6 493 17.8 471 Comparative Example 3 19.5 414 16.3 412
[0122] It can be seen from Table 1 above that the solid tire prepared by the present invention has good mechanical properties and a high wear resistance index, thereby extending the service life of the tire.
[0123] The tread rubbers prepared in Example 1 and Comparative Examples 1-3 were tested for anti-skid performance. The friction coefficients of dry grinding and wet grinding (smooth mode) were tested according to standard TM144:2011. The SRA and SRB friction coefficients (smooth mode) were tested according to standard ISO13287:2012. SRA is the friction coefficient of the tile interface contaminated by detergent (i.e., containing surfactants), and SRB is the friction coefficient of the steel plate interface contaminated by glycerol solution. The test results are shown in Table 2 below:
[0124] Table 2
[0125] Dry grinding Wet grinding SRA SRB Example 1 0.99 0.94 0.67 0.71 Comparative Example 1 0.94 0.88 0.56 0.61 Comparative Example 2 0.92 0.83 0.51 0.54 Comparative Example 3 0.91 0.81 0.48 0.52
[0126] It can be seen from Table 2 above that the friction coefficient of the tread rubber prepared in the present invention is significantly greater than that of Comparative Examples 1-3, especially the friction coefficient of wet grinding, which indicates that the solid tire prepared in the present invention has good anti-wet skid performance.
[0127] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A solid tire, characterized in that: Including tire liner and tread rubber; The tire liner comprises the following raw materials in parts by weight: 80-100 parts of natural rubber, 40-50 parts of butadiene rubber, 15-25 parts of carbon black, 2-4 parts of vulcanizing agent, 3-6 parts of zinc oxide, 2-5 parts of stearic acid, 1-2 parts of silane coupling agent, 0.5-1.5 parts of accelerator, and 0.5-0.8 parts of antioxidant; The tread rubber comprises the following raw materials in parts by weight: 60-80 parts of natural rubber, 40-50 parts of styrene-butadiene rubber, 20-30 parts of nitrile rubber, 5-10 parts of ethylene-propylene rubber, 1-3 parts of vulcanizer, 0.5-2 parts of accelerator, 25-35 parts of modified carbon black, 15-30 parts of anti-skid and wear-resistant agent, 2-5 parts of zinc oxide, 3-6 parts of stearic acid, 3-5 parts of filler oil and 0.4-0.7 parts of antioxidant.
2. The solid tire according to claim 1, characterized in that: The vulcanizing agent is sulfur; the silane coupling agent is one or more of KH550, KH560, and KH570; the accelerator is one or more of accelerator D, accelerator CZ, accelerator TMTM, and accelerator TMTD; the filler oil is cyclohexane oil or white oil; the antioxidant is one or more of antioxidant 4020, antioxidant RD, and antioxidant NA.
3. The solid tire according to claim 1, characterized in that: The method for preparing the anti-skid and wear-resistant filler comprises the following steps: S1, adding carbon fiber to deionized water, then adding melamine, boric acid, ammonium molybdate, and sodium dodecyl sulfate, stirring to react, filtering, washing, drying, and calcining under a nitrogen atmosphere to obtain composite carbon fiber; S2, adding the composite carbon fiber in step S1 to an ethanol aqueous solution, then adding γ-glycidyloxypropyltrimethoxysilane, heating to react, filtering, washing, and drying after the reaction is completed to obtain a modified carbon fiber; S3, adding toluene to the modified carbon fiber in step S2, and then adding phenolic resin and triethylamine, and reacting at a constant temperature under a nitrogen atmosphere. After the reaction is completed, filtering, washing, and drying are performed to obtain the wear-resistant and anti-skid filler.
4. The solid tire according to claim 3, characterized in that: In step S1, the mass ratio of carbon fiber, melamine, boric acid, ammonium molybdate and sodium dodecyl sulfate is 50-60:30-40:15-20:20-30:10-20, the stirring reaction temperature is 90-100° C., and the time is 4-6 hours; the calcination temperature is 800-900° C., and the time is 3-5 hours.
5. The solid tire according to claim 3, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution in step S2 is 7-8:2-3, the mass ratio of the composite carbon fiber and γ-glycidyloxypropyltrimethoxysilane is 50-60:4-8, the temperature of the heating reaction is 50-60°C, and the time is 2-3h.
6. The solid tire according to claim 3, characterized in that: In step S3, the mass ratio of the modified carbon fiber, phenolic resin and triethylamine is 50-60:20-30:30-40, the temperature of the isothermal reaction is 70-80° C., and the time is 1-3 hours.
7. The solid tire according to claim 1, characterized in that: The preparation method of the modified carbon black is as follows: 20-30g of zirconium oxychloride is added to 200-300g of hydrochloric acid solution with a mass concentration of 5%, and then 50g of carbon black is added. After stirring evenly, ammonia water with a mass concentration of 10% is added to adjust the pH to 9-10, and the mixture is stirred at 30-40°C for 2-3h. After stirring, the mixture is filtered, dried, and calcined under a nitrogen atmosphere to obtain composite carbon black; 50-60g of composite carbon black is added to 800mL of ethanol aqueous solution with a volume ratio of 8:2, and then 5-10g of γ-aminopropyltriethoxysilane is added. The mixture is stirred at 60-70°C for 2-3h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain amino carbon black; 50-60g of amino carbon black is added to DMF, and then 5-10g of 2-(trifluoromethyl)cinnamic acid and 1-3g of p-toluenesulfonic acid are added. The mixture is reacted at 90-100°C for 3-4h. After the reaction is completed, the modified carbon black is obtained.
8. A method for preparing a solid tire according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of tire liner: weigh raw materials according to the formula, add natural rubber and butadiene rubber into an open mill, mix them once, then add carbon black, zinc oxide, stearic acid, silane coupling agent, and antioxidant, mix them twice, then add vulcanizing agent and accelerator, mix them three times, and after mixing, add the tire rubber into a mold to obtain a tire liner; (2) Preparation of tread rubber: weighing raw materials according to the formula, adding natural rubber, styrene-butadiene rubber, nitrile rubber, and ethylene-propylene rubber into an open mill, mixing once, then adding antioxidant, modified carbon black, anti-skid and wear-resistant agent, zinc oxide, stearic acid, and filler oil, mixing twice, then adding vulcanizing agent and accelerator, mixing three times, after mixing, adding the tread rubber material into a mold to obtain a tread rubber layer; (3) Preparation of solid tire: a layer of glue is applied on the outside of the tire inner liner, the tread rubber layer is adhered to the tire inner liner, and the tire is kept warm at 50-60°C for 2-4 hours, and then placed in a mold and vulcanized to obtain the solid tire.
9. The preparation method according to claim 7, characterized in that: In step (1), the temperature of the first mixing is 60-70°C, and the time is 5-8 minutes, the temperature of the second mixing is 60-70°C, and the time is 6-10 minutes, and the temperature of the third mixing is 140-160°C, and the time is 10-15 minutes; in step (2), the temperature of the first mixing is 60-70°C, and the time is 5-8 minutes, the temperature of the second mixing is 70-80°C, and the time is 4-6 minutes, and the temperature of the third mixing is 120-140°C, and the time is 10-15 minutes; in step (3), the vulcanization temperature is 140-160°C, and the time is 3-5 hours.
10. An industrial forklift solid tire, characterized in that: The solid tire is prepared using the solid tire described in any one of claims 1 to 7.
Citation Information
Patent Citations
Solid tire composition prepared by using tire offcuts
CN102504379A
Durable solid tire and preparation method thereof
CN114163703A
Wear-resistant heat-resistant tire tread rubber
CN110746664A
Antiskid sole and production process thereof
CN113248801A
Flame-retardant weather-resistant stone-like coating and preparation method thereof
CN117447908A
